(2x-6)-(3x-4)=-(-4x+x)-4x+6

Simple and best practice solution for (2x-6)-(3x-4)=-(-4x+x)-4x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-6)-(3x-4)=-(-4x+x)-4x+6 equation:


Simplifying
(2x + -6) + -1(3x + -4) = -1(-4x + x) + -4x + 6

Reorder the terms:
(-6 + 2x) + -1(3x + -4) = -1(-4x + x) + -4x + 6

Remove parenthesis around (-6 + 2x)
-6 + 2x + -1(3x + -4) = -1(-4x + x) + -4x + 6

Reorder the terms:
-6 + 2x + -1(-4 + 3x) = -1(-4x + x) + -4x + 6
-6 + 2x + (-4 * -1 + 3x * -1) = -1(-4x + x) + -4x + 6
-6 + 2x + (4 + -3x) = -1(-4x + x) + -4x + 6

Reorder the terms:
-6 + 4 + 2x + -3x = -1(-4x + x) + -4x + 6

Combine like terms: -6 + 4 = -2
-2 + 2x + -3x = -1(-4x + x) + -4x + 6

Combine like terms: 2x + -3x = -1x
-2 + -1x = -1(-4x + x) + -4x + 6

Combine like terms: -4x + x = -3x
-2 + -1x = -1(-3x) + -4x + 6

Remove parenthesis around (-3x)
-2 + -1x = -1 * -3x + -4x + 6

Multiply -1 * -3
-2 + -1x = 3x + -4x + 6

Reorder the terms:
-2 + -1x = 6 + 3x + -4x

Combine like terms: 3x + -4x = -1x
-2 + -1x = 6 + -1x

Add 'x' to each side of the equation.
-2 + -1x + x = 6 + -1x + x

Combine like terms: -1x + x = 0
-2 + 0 = 6 + -1x + x
-2 = 6 + -1x + x

Combine like terms: -1x + x = 0
-2 = 6 + 0
-2 = 6

Solving
-2 = 6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -5.2p=-9-8.9p | | 2X-24=X+5 | | 200-150= | | 12x+7=6x+7 | | 58r=1460 | | 10+c=13 | | D^6+9D^4+24D+16=0 | | 9x-7=-9 | | c^3-f^3=0 | | 9=-6 | | -21+kj=15 | | 15f=240 | | 8(x+5)+2=-7(x-3)-2 | | -4x=452 | | 16t^2-5184=0 | | a+b+c=123+2 | | -3a^5+18a^4-27a^3=0 | | -20.5-2.2b=-7.2b | | 12x-8(5)=12 | | 3x+24=18+16x-128 | | 4x^2+20x-21=0 | | 16t^2-112t-960=0 | | 4x^2+30x-21=0 | | 12=4x-0 | | 85x+104x=2700 | | x=(x^2-1x-10) | | 8.2+(-8.2)=0 | | f(x)=-9x^2+7x+4 | | 6x+3=4x+35 | | 33+3y-7=13y-9-5y | | 1.7=4c+0.3+5c+0.5 | | y=10x^2-15x+7 |

Equations solver categories